INOVASI SISTEM INFORMASI TENAGA KESEHATAN (SINAKES) ONLINE PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA SEMARANG - Nurul Lutfiana; Endang Larasati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
The government which is responsible for implementing the State is required to improve the quality of public services so that the fulfillment of community needs can run well. One way the government can escalate this quality of public services is by creating an innovation. As an effort to improve public services in the field of licensing of health personnel, DPM-PTSP Semarang established a